A GMP-compliant protocol to expand and transfect cancer patient T cells with mRNA encoding a tumor-specific chimeric antigen receptor - Krug, Christian; Wiesinger, Manuel; Abken, Hinrich; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (Cancer Immunology Immunotherapy, 2014)
Chimeric antigen receptors (CARs), which combine an antibody-derived binding domain (single chain fragment variable) with T-cell-activating signaling domains, have become a promising tool in the adoptive cellular therapy of cancer. Retro- and lenti-viral transductions are currently the standard methods to equip T cells with a CAR; permanent CAR expression, however, harbors several risks like uncontrolled auto-reactivity. Modification of T cells by electroporation with CAR-encoding RNA to achieve transient expression likely circumvents these difficulties. We here present a GMP-compliant protocol to activate and expand T cells for clinical application. The protocol is optimized in particular to produce CAR-modified T cells in clinically sufficient numbers under full GMP-compliance from late-stage cancer patients. This protocol allows the generation of 6.7 × 10(8) CAR-expressing T cells from one patient leukapheresis. The CAR-engineered T cells produced pro-inflammatory cytokines after stimulation with antigen-bearing tumor cells and lysed tumor cells in an antigen-specific manner. This functional capacity was maintained after cryopreservation. Taken together, we provide a clinically applicable protocol to transiently engineer sufficient numbers of antigen-specific patient T cells for use in adoptive cell therapy of cancer.
EVALuna2:19440

A new method to monitor antigen-specific CD8+ T cells, avoiding additional target cells and the restriction to human leukocyte antigen haplotype. - Prommersberger, S.; Hoefflin, S.; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (Gene Therapy, 2015)
Therapeutic vaccination of cancer patients with dendritic cells aims at inducing a strong tumor-specific T-cell response. Testing new target antigens for their immunogenicity is crucial to evaluate their suitability for this approach. Here we demonstrate a comfortable and reliable method to detect antigen-specific CD8(+) T-cell responses without the knowledge of the precise T-cell epitope and without the usage of additional target cells. We used the CD8(+) T cells themselves and electroporated them with RNA encoding the respective tumor antigen. The cells expressed, processed and presented the antigen and were capable of stimulating each other in functional readouts. For the model antigen MelanA, the number of interferon-?-secreting cells obtained with this method highly correlated with the numbers obtained by exogenous peptide loading (R(2)=0.8). The method was also applicable for the tumor-associated antigen Wilms' tumor protein 1. This system is quick and easy to perform, independent of the donors human leukocyte antigen type and circumvents the need for additional cells as targets. It can be used in preclinical research to test new antigens for their immunogenic potential and for immunomonitoring in cancer patients.
EVALuna2:19552

A One-Armed Phase I Dose Escalation Trial Design: Personalized Vaccination with IKKβ-Matured, RNA-Loaded Dendritic Cells for Metastatic Uveal Melanoma - Koch, Elias; Schaft, Niels; Kummer, Mirko; Berking, Carola; Schuler, Gerold; Hasumi, Kenichiro; Dörrie, Jan; Schuler-Thurner, Beatrice (Frontiers in Immunology, 2022)
Uveal melanoma (UM) is an orphan disease with a mortality of 80% within one year upon the development of metastatic disease. UM does hardly respond to chemotherapy and kinase inhibitors and is largely resistant to checkpoint inhibition. Hence, further therapy approaches are urgently needed. To improve clinical outcome, we designed a trial employing the 3rd generation personalized IKKβ-matured RNA-transfected dendritic cell (DC) vaccine which primes T cells and in addition activates NK cells. This ongoing phase I trial [NCT04335890 (www.clinicaltrials.gov), Eudract: 2018-004390-28 (www.clinicaltrialsregister.eu)] investigates patients with treatment-naive metastatic UM. Monocytes are isolated by leukapheresis, differentiated to immature DCs, matured with a cytokine cocktail, and activated via the NF-κB pathway by electroporation with RNA encoding a constitutively active mutant of IKKβ. Three types of antigen-RNA are co-electroporated: i) amplified mRNA of the tumor representing the whole transcriptome, ii) RNA encoding driver mutations identified by exome sequencing, and iii) overexpressed non-mutated tumor antigens detected by transcriptome sequencing. This highly personalized DC vaccine is applied by 9 intravenous infusions in a staggered schedule over one year. Parallel to the vaccination, standard therapy, usually an immune checkpoint blockade (ICB) as mono (anti-PD-1) or combined (anti-CTLA4 and anti-PD-1) regimen is initiated. The coordinated vaccine-induced immune response encompassing tumor-specific T cells and innate NK cells should synergize with ICB, perhaps resulting in measurable clinical responses in this resistant tumor entity. Primary outcome measures of this trial are safety, tolerability and toxicity; secondary outcome measures comprise overall survival and induction of antigen-specific T cells.
CRIS-Team Scopus Importer:2022-03-04
Keywords: IKKβ-matured dendritic cells; Immune checkpoint blockade; metastatic uveal melanoma; personalized vaccine; tumor antigen vaccine; tumor antigens

Arming T cells with a gp100-specific TCR and a CSPG4-specific CAR using combined DNA-and RNA-based receptor transfer - Simon, Bianca; Harrer, Dennis C.; Schuler-Thurner, Beatrice; Schuler, Gerold; Uslu, Ugur (Cancers, 2019)
Tumor cells can develop immune escape mechanisms to bypass T cell recognition, e.g., antigen loss or downregulation of the antigen presenting machinery, which represents a major challenge in adoptive T cell therapy. To counteract these mechanisms, we transferred not only one, but two receptors into the same T cell to generate T cells expressing two additional receptors (TETARs). We generated these TETARs by lentiviral transduction of a gp100-specific T cell receptor (TCR) and subsequent electroporation of mRNA encoding a second-generation CSPG4-specific chimeric antigen receptor (CAR). Following pilot experiments to optimize the combined DNA-and RNA-based receptor transfer, the functionality of TETARs was compared to T cells either transfected with the TCR only or the CAR only. After transfection, TETARs clearly expressed both introduced receptors on their cell surface. When stimulated with tumor cells expressing either one of the antigens or both, TETARs were able to secrete cytokines and showed cytotoxicity. The confirmation that two antigen-specific receptors can be functionally combined using two different methods to introduce each receptor into the same T cell opens new possibilities and opportunities in cancer immunotherapy. For further evaluation, the use of these TETARs in appropriate animal models will be the next step towards a potential clinical use in cancer patients.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Antigen loss; Cancer; Chimeric antigen receptor; Electroporation; Immune escape; Immunotherapy; Lentiviral transduction; Lentivirus; Melanoma

Autologous regulatory T-cell transfer in refractory ulcerative colitis with concomitant primary sclerosing cholangitis - Voskens, Caroline; Stoica, Diane; Rosenberg, Marita; Vitali, Francesco; Zundler, Sebastian; Ganslmayer, Marion; Knott, Heike; Wiesinger, Manuel; Wunder, Jutta; Kummer, Mirko; Siegmund, Britta; Schnoy, Elisabeth; et al. (Gut, 2022)
Objective Ulcerative colitis (UC) is a chronic, debilitating immune-mediated disease driven by disturbed mucosal homeostasis, with an excess of intestinal effector T cells and an insufficient expansion of mucosal regulatory T cells (Tregs). We here report on the successful adoptive transfer of autologous, ex vivo expanded Tregs in a patient with refractory UC and associated primary sclerosing cholangitis (PSC), for which effective therapy is currently not available.
CRIS-Team WoS Importer:2022-04-29

Automated closed-system manufacturing of human monocyte-derived dendritic cells for cancer immunotherapy - Erdmann, Michael; Uslu, Ugur; Wiesinger, Manuel; Bruening, Mareke; Altmann, Tobias; Strasser, Erwin; Schuler, Gerold; Schuler-Thurner, Beatrice (Journal of Immunological Methods, 2018)
Dendritic cell (DC)-based vaccines have been successfully used for immunotherapy of cancer and infections. A major obstacle is the need for high-level class A cleanroom cGMP facilities for DC generation. The CliniMACS Prodigy® (Prodigy) represents a new platform integrating all GMP-compliant manufacturing steps in a closed system for automated production of various cellular products, notably T cells, NK cells and CD34+ cells. We now systematically tested its suitability for producing human mature monocyte-derived DCs (Mo-DCs), and optimized it by directly comparing the Prodigy approach to our established standard production of Mo-DCs from elutriated monocytes in dishes or bags. Upon step-by-step identification of an optimal cell concentration for the Prodigy's CentriCult culture chamber, the total yield (% of input CD14+ monocytes), phenotype, and functionality of mature Mo-DCs were equivalent to those generated by the standard protocol. Technician's labor time was comparable for both methods, but the Prodigy approach significantly reduced hands-on time and high-level clean room resources. In summary, using our optimized conditions for the CliniMACS Prodigy, human Mo-DCs for clinical application can be generated almost automatically in a fully closed system. A significant drawback of the Prodigy approach was, however, that due to the limited size of the CentriCult culture chamber, in contrast to our standard semi-closed elutriation approach, only one fourth of an apheresis could be processed at once.
EVALuna2:203616

Automated Good Manufacturing Practice–compliant generation of human monocyte-derived dendritic cells from a complete apheresis product using a hollow-fiber bioreactor system overcomes a major hurdle in the manufacture of dendritic cells for cancer vaccines - Uslu, Ugur; Erdmann, Michael; Wiesinger, Manuel; Schuler, Gerold; Schuler-Thurner, Beatrice (Cytotherapy, 2019)
Background: Although dendritic cell (DC)–based cancer vaccines represent a promising treatment strategy, its exploration in the clinic is hampered due to the need for Good Manufacturing Practice (GMP) facilities and associated trained staff for the generation of large numbers of DCs. The Quantum bioreactor system offered by Terumo BCT represents a hollow-fiber platform integrating GMP-compliant manufacturing steps in a closed system for automated cultivation of cellular products. In the respective established protocols, the hollow fibers are coated with fibronectin and trypsin is used to harvest the final cell product, which in the case of DCs allows processing of only one tenth of an apheresis product. Materials and Results: We successfully developed a new protocol that circumvents the need for fibronectin coating and trypsin digestion, and makes the Quantum bioreactor system now suitable for generating large numbers of mature human monocyte-derived DCs (Mo-DCs) by processing a complete apheresis product at once. To achieve that, it needed a step-by-step optimization of DC-differentiation, e.g., the varying of media exchange rates and cytokine concentration until the total yield (% of input CD14+ monocytes), as well as the phenotype and functionality of mature Mo-DCs, became equivalent to those generated by our established standard production of Mo-DCs in cell culture bags. Conclusions: By using this new protocol for the Food and Drug Administration–approved Quantum system, it is now possible for the first time to process one complete apheresis to automatically generate large numbers of human Mo-DCs, making it much more feasible to exploit the potential of individualized DC-based immunotherapy.
CRIS-Team Scopus Importer:2019-11-12
Keywords: adoptive cell transfer; cell therapy; cellular therapy; dendritic cell vaccine; dendritic cells; immunotherapy; monocyte-derived dendritic cells; vaccines

Block Excision of Iridociliary Tumors Enables Molecular Profiling and Immune Vaccination - Heindl, Ludwig M.; Koch, Konrad R.; Hermann, Manuel M.; Merkelbach-Bruse, Sabine; Schultheis, Anne M.; Wagener, Svenja; Buettner, Reinhard; Mauch, Cornelia; Schuler-Thurner, Beatrice; Schuler, Gerold; Cursiefen, Claus (Ophthalmology, 2017)
EVALuna2:34326

Blood eosinophilia is an on-treatment biomarker in patients undergoing vaccination with dendritic cells that correlates with long-term patient outcome - Moreira, Alvaro; Vass, V.; Erdmann, M.; Sponagl, F.; Schuler, Gerold; Schuler-Thurner, Beatrice (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Blood eosinophilia is an on-treatment biomarker in patients with solid tumors undergoing dendritic cell vaccination with autologous tumor-RNA - Moreira, Alvaro; Erdmann, Michael; Uslu, Ugur; Vass, Verona; Schuler, Gerold; Schuler-Thurner, Beatrice (Pharmaceutics, 2020)
Background: The approvals of immune checkpoint inhibitors for several cancer types and the rapidly growing recognition that T cell-based immunotherapy significantly improves outcomes for cancer patients led to a re-emergence of cancer vaccines, including dendritic cell (DC)-based immunotherapy. Blood and tissue biomarkers to identify responders and long-term survivors and to optimize cost and cost-effectiveness of treatment are greatly needed. We wanted to investigate whether blood eosinophilia is a predictive biomarker for patients with solid tumors receiving vaccinations with DCs loaded with autologous tumor-RNA. Methods: In total, 67 patients with metastatic solid tumors, who we treated with autologous monocyte-derived DCs transfected with total tumor mRNA, were serially analyzed for eosinophil counts and survival over the course of up to 14 years. Eosinophilic counts were performed on peripheral blood smears. Results: Up to 87% of the patients treated with DC-based immunotherapy experienced at least once an eosinophilia of ≥ 5% after initiation of therapy; 61 % reached levels of ≥ 10% eosinophils, and 13% of patients showed eosinophil counts of 20% or above. While prevaccination eosinophil levels were not associated with survival, patients with blood eosinophilia at any point after initiation of DC-based immunotherapy showed a trend towards longer survival. There was a statistically significant difference for the patients with eosinophil counts of 20% or more (p = 0.03). In those patients, survival was prolonged to a median of 58 months (range 2-111 months), compared to a median of 20 months (range 0-119 months) in patients with lower eosinophil counts. In 12% of the patients, an immediate increase in eosinophil count of at least 10 percentage points could be detected after the first vaccine, which also appeared to correlate with survival (65 vs. 24 months; p = 0.06). Conclusion: Blood eosinophilia appears to be an early, on-therapy biomarker in patients with solid tumors undergoing vaccination with RNA-transfected DC, specifically autologous tumor mRNA-transfected DC vaccines, and it correlates with long-term patient outcome. Eosinophilia should be systematically investigated in future trials.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Biomarkers; Dendritic cell vaccines; Eosinophils

Clinical determinants of long-term survival in metastatic uveal melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Erdmann, Michael; Heinzerling, Lucie; Hohberger, Bettina; Knorr, Harald; Leiter, Ulrike; Meier, Friedegund; Mohr, Peter; Rahimi, Farnaz; et al. (Cancer Immunology, Immunotherapy, 2021)
This study aimed to identify prognostic factors in patients with metastatic uveal melanoma (UM) that were associated with long-term survival in a real-world setting. A total of 94 patients with metastatic UM were included from German skin cancer centers and the German national skin cancer registry (ADOReg). Data were analyzed for the response to treatment, progression-free survival, and overall survival (OS). Prognostic factors were explored with univariate Cox regression, log-rank, and χ2-tests. Identified factors were subsequently validated after the population was divided into two cohorts of short-term survival (< 2 years OS, cohort A, n = 50) and long-term survival (> 2 years OS, cohort B, n = 44). A poor ECOG performance status (hazard ratio [HR] 2.0, 95% confidence interval [CI] 1.0–3.9) and elevated serum LDH (HR 2.0, 95% CI 1.0–3.8) were associated with a poor OS, whereas a good response to immune checkpoint blockade (ICB, p < 0.001), radiation therapy (p < 0.001), or liver-directed treatments (p = 0.01) were associated with a prolonged OS. Long-term survivors (cohort B) showed a higher median number of organs affected by metastasis (p < 0.001), while patients with liver metastases only were more common in cohort A (40% vs. 9%; p = 0.002). A partial response to ICB was observed in 16% (12/73), being 21% (8/38) for combined ICB, 17% (1/6) for single CTLA4 inhibition, and 10% (3/29) for single PD1 inhibition. One complete response occurred in cohort B with combined ICB. We conclude that the response to ICB and the presence of extrahepatic disease were favorable prognostic factors for long-term survival.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Immune checkpoint blockade; Liver metastases; Liver-directed treatment; Long-term survival; Registry; Uveal melanoma

Clinical Prognostic Factors in metastatic Choroidal Melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, E.; Erdmann, Michael; Heinzerling, L.; Hohberger, Bettina; Knorr, H.; Leiter-Stoppke, U.; Meier, F.; Mohr, P.; Rahimi, F.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Clinical-Scale Production of CAR-T Cells for the Treatment of Melanoma Patients by mRNA Transfection of a CSPG4-Specific CAR under Full GMP Compliance. - Wiesinger, Manuel; Maerz, Johannes; Kummer, Mirko; Schuler, Gerold; Dörrie, Jan; Schuler-Thurner, Beatrice; Schaft, Niels (Cancers, 2019)
Chimeric antigen receptor (CAR)-T cells already showed impressive clinical regressions in leukemia and lymphoma. However, the development of CAR-T cells against solid tumors lags behind. Here we present the clinical-scale production of CAR-T cells for the treatment of melanoma under full GMP compliance. In this approach a CAR, specific for chondroitin sulfate proteoglycan 4 (CSPG4) is intentionally transiently expressed by mRNA electroporation for safety reasons. The clinical-scale protocol was optimized for: (i) expansion of T cells, (ii) electroporation efficiency, (iii) viability, (iv) cryopreservation, and (v) potency. Four consistency runs resulted in CAR-T cells in clinically sufficient numbers, i.e., 2.4 x 10(9) CAR-expressing T cells, starting from 1.77x10(8)PBMCs, with an average expansion of 13.6x, an electroporation efficiency of 88.0% CAR-positive cells, a survival of 74.1% after electroporation, and a viability of 84% after cryopreservation. Purity was 98.7% CD3(+) cells, with 78.1% CD3(+)/CD8(+) T cells and with minor contaminations of 1.2% NK cells and 0.6% B cells. The resulting CAR-T cells were tested for cytolytic activity after cryopreservation and showed antigen-specific and very efficient lysis of tumor cells. Although our work is descriptive rather than investigative in nature, we expect that providing this clinically applicable protocol to generate sufficient numbers of mRNA-transfected CAR-T cells will help in moving the field of adoptive cell therapy of cancer forward.
CRIS-Team WoS Importer:2019-09-24

Combined cytotoxic activity of an infectious, but non-replicative herpes simplex virus type 1 and plasmacytoid dendritic cells against tumour cells - Thomann, Sabrina; Boscheinen, Jan; Vogel, Karin; Knipe, David M.; Deluca, Neal; Gross, Stefanie; Schuler-Thurner, Beatrice; Schuster, Philipp; Schmidt, Barbara (Immunology, 2015)
Malignant melanoma is an aggressive tumour of the skin with increasing incidence, frequent metastasis and poor prognosis. At the same time, it is an immunogenic type of cancer with spontaneous regressions. Most recently, the tumoricidal effect of plasmacytoid dendritic cells (pDC) and their capacity to overcome the immunosuppressive tumour microenvironment are being investigated. In this respect, we studied the effect of the infectious, but replication-deficient, herpes simplex virus 1 (HSV-1) d106S vaccine strain, which lacks essential immediate early genes, in pDC co-cultures with 11 melanoma cell lines. We observed a strong cytotoxic activity, inducing apoptotic and necrotic cell death in most melanoma cell lines. The cytotoxic activity of HSV-1 d106S plus pDC was comparable to the levels of cytotoxicity induced by natural killer cells, but required only a fraction of cells with effector : target ratios of 1 : 20 (P < 0·05). The suppressive activity of cell-free supernatants derived from virus-stimulated pDC was significantly neutralized using antibodies against the interferon-? receptor (P < 0·05). In addition to type I interferons, TRAIL and granzyme B contributed to the inhibitory effect of HSV-1 d106S plus pDC to a minor extent. UV-irradiated viral stocks were significantly less active than infectious particles, both in the absence and presence of pDC (P < 0·05), indicating that residual activity of HSV-1 d106S is a major component and sensitizes the tumour cells to interferon-producing pDC. Three leukaemic cell lines were also susceptible to this treatment, suggesting a general anti-tumour effect. In conclusion, the potential of HSV-1 d106S for therapeutic vaccination should be further evaluated in patients suffering from different malignancies.
EVALuna2:8282

Comparison of the oncolytic activity of a replication-competent and a replication-deficient herpes simplex virus 1 - Lindner, Georg; Walter, Annika; Magnus, Clara L.; Rosenhammer, Katharina; Holoborodko, Bohdan; Koch, Victoria; Hirsch, Sarah; Grossmann, Luis; Li, Suqi; Knipe, David M.; DeLuca, Neal; Schuler-Thurner, Beatrice; et al. (Immunology, 2024)
In 2015, the oncolytic herpes simplex virus 1 (HSV-1) T-VEC (talimogene laherparepvec) was approved for intratumoral injection in non-resectable malignant melanoma. To determine whether viral replication is required for oncolytic activity, we compared replication-deficient HSV-1 d106S with replication-competent T-VEC. High infectious doses of HSV-1 d106S killed melanoma (n = 10), head-and-neck squamous cell carcinoma (n = 11), and chondrosarcoma cell lines (n = 2) significantly faster than T-VEC as measured by MTT metabolic activity, while low doses of T-VEC were more effective over time. HSV-1 d106S and, to a lesser extent T-VEC, triggered caspase-dependent early apoptosis as shown by pan-caspase inhibition and specific induction of caspases 3/7, 8, and 9. HSV-1 d106S induced a higher ratio of apoptosis-inducing infected cell protein (ICP) 0 to apoptosis-blocking ICP6 than T-VEC. T-VEC was oncolytic for an extended period of time as viral replication continued, which could be partially blocked by the antiviral drug aciclovir. High doses of T-VEC, but not HSV-1 d106S, increased interferon-β mRNA as part of the intrinsic immune response. When markers of immunogenic cell death were assessed, ATP was released more efficiently in the context of T-VEC than HSV-1 d106S infection, whereas HMGB1 was induced comparatively well. Overall, the early oncolytic effect on three different tumour entities was stronger with the non-replicative strain, while the replication-competent virus elicited a stronger innate immune response and more pronounced immunogenic cell death.
CRIS-Team Scopus Importer:2024-03-15
Keywords: apoptosis; cancer; human; tumour immunology; viral

Comparison of the Serum Tumor Markers S100 and Melanoma-inhibitory Activity (MIA) in the Monitoring of Patients with Metastatic Melanoma Receiving Vaccination Immunotherapy with Dendritic Cells - Uslu, Ugur; Schliep, Stefan; Schliep, Klaus; Erdmann, Michael; Koch, Hans-Uwe; Parsch, Hans; Rosenheinrich, Stina; Anzengruber, Doris; Boßerhoff, Anja Katrin; Schuler, Gerold; Schuler-Thurner, Beatrice (Anticancer Research, 2017)
In patients with melanoma, early dissemination via lymphatic and hematogenous routes is frequently seen. Thus, besides clinical follow-up examination and imaging, reliable melanoma-specific serological tumor markers are needed.We retrospectively compared two serum markers for melanoma, S100 and melanoma-inhibitory activity (MIA), for monitoring of patients with metastatic melanoma under either adjuvant or therapeutic vaccination immunotherapy with dendritic cells (DC). Serum was obtained from a total of 100 patients (28 patients in stage III and 72 patients in stage IV, according to the American Joint Committee on Cancer 2002) at regular intervals during therapy, accompanied by follow-up imaging.When relapse was detected, both markers often remained within normal range. In contrast, in patients with metastatic measurable disease receiving therapeutic and not adjuvant DC vaccination, an increase of both markers was a strong indicator for disease progression. When comparing both markers in the whole study population, MIA showed a superior sensitivity to detect disease progression.S100 and MIA are highly sensitive tumor markers for monitoring of patients with melanoma with current metastases, but less sensitive for monitoring of tumor-free patients. In the current study, MIA had a slightly superior sensitivity to detect progressive disease compared to S100 and seems to be more useful in monitoring of patients with metastatic melanoma receiving immunotherapy.
EVALuna2:4755

Concurrent interaction of DCs with CD4(+) and CD8(+) T cells improves secondary CTL expansion: It takes three to tango. - Hoyer, Stefanie; Prommersberger, Sabrina; Pfeiffer, Isabell; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (European Journal of Immunology, 2014)
T-cell help is essential for CTL-memory formation. Nevertheless, it is unclear whether the continuous presence of CD4(+) T-helper (Th) cells is required during dendritic cell (DC)/CD8(+) T-cell encounters, or whether a DC will remember the helper signal after the Th cell has departed. This question is relevant for the design of therapeutic cancer vaccines. Therefore, we investigated how human DCs need to interact with CD4(+) T cells to mediate efficient repetitive CTL expansion in vitro. We established an autologous antigen-specific in vitro system with monocyte-derived DCs, as these are primarily used for cancer vaccination. Contrary to common belief, a sequential interaction of licensed DCs with CD8(+) T cells barely improved CTL expansion. In sharp contrast, simultaneous encounter of Th cells and CTLs with the same DC during the first in vitro encounter is a prerequisite for optimal subsequent CTL expansion in our in vitro system. These data suggest that, in contrast to DC maturation, the activation of DCs by Th cells, which is necessary for optimal CTL stimulation, is transient. This knowledge has significant implications for the design of new and more effective DC-based vaccination strategies. Furthermore, our in vitro system could be a valuable tool for preclinical immunotherapeutical studies.
EVALuna2:19507

Conventional and three-dimensional photography as a tool to map distribution patterns of in-transit melanoma metastases on the lower extremity - Müller, Kilian; Berking, Carola; Voskens, Caroline; Heppt, Markus; Heinzerling, Lucie; Koch, Elias; Kramer, Rafaela; Merkel, Susanne; Schuler-Thurner, Beatrice; Schellerer, Vera; Steeb, Theresa; Wessely, Anja; et al. (Frontiers in Medicine, 2023)
Background: In melanoma, in-transit metastases characteristically occur at the lower extremity along lymphatic vessels. Objectives: The objective of this study was to evaluate conventional or three-dimensional photography as a tool to analyze in-transit metastasis pattern of melanoma of the lower extremity. In addition, we assessed risk factors for the development of in-transit metastases in cutaneous melanoma. Methods: In this retrospective, monocentric study first we compared the clinical data of all evaluable patients with in-transit metastases of melanoma on the lower extremity (n = 94) with melanoma patients without recurrence of disease (n = 288). In addition, based on conventional (n = 24) and three-dimensional photography (n = 22), we defined the specific distribution patterns of the in-transit metastases on the lower extremity. Results: Using a multivariate analysis we identified nodular melanoma, tumor thickness, and ulceration as independent risk factors to develop in-transit metastases ITM (n = 94). In patients with melanoma on the lower leg (n = 31), in-transit metastases preferentially developed along anatomically predefined lymphatic pathways. In contrast when analyzing in-transit metastases of melanoma on the foot (n = 15) no clear pattern could be visualized. In addition, no difference in distance between in-transit metastases and primary melanoma on the foot compared to the lower leg was observed using three-dimensional photography (n = 22). Conclusion: A risk-adapted follow-up of melanoma patients to detect in-transit metastases can be applied by knowledge of the specific lymphatic drainage of the lower extremity. Our current analysis suggests a more complex lymphatic drainage of the foot.
CRIS-Team Scopus Importer:2023-02-10
Keywords: 3D photography; in-transit metastasis; lower extremity; lymphatic pathways; melanoma

Effectiveness and tolerability of ipilimumab: experiences from 198 patients included in a named-patient program in various daily-practice settings and multiple institutions - Eigentler, Thomas K.; Schlaak, Max; Hassel, Jessica C.; Loquai, Carmen; Stoffels, Ingo; Gutzmer, Ralf'; Paetzold, Sylvie; Mohr, Peter; Keller, Ulrich; Starz, Hans; Ulrich, Jens; Tsianakas, Athanasios; et al. (Journal of Immunotherapy, 2014)
Ipilimumab is an approved anti-cytotoxic T-lymphocyte-associated antigen-4 monoclonal antibody introducing immune responses in melanoma patients. Treatment experiences from named-patient programs support the evaluation of the efficacy and tolerability of new medicines under usual circumstances of health care practice. Here, the largest ever reported cohort treated with ipilimumab 3 mg/kg alone is described.This report retrospectively analyzes data of 198 patients who were followed up in 15 hospital centers in Germany between April 2010 and March 2013. Patients had received prior therapy for unresectable stage III or IV melanoma before receiving ipilimumab (4 doses of 3 mg/kg every 21 d). Routine staging and tumor response evaluation procedures were applied.Of the patients, 119 received the planned 4-course therapy schedule; in further 79 patients, the number of doses was reduced mainly because of toxicity or fast progression. In all, 196 patients were eligible for evaluation of the efficacy of ipilimumab under routine care conditions. Median overall survival (OS) was 6.8 months [95% confidence interval, 5.6-10.3] from the start of therapy. OS differed significantly among patients who received 4 doses (n=119) and those receiving <4 doses (n=79) (14.2 vs. 2.0 mo; P<0.0001). The overall response rate (ORR) of 11% was in the same range as reported from previous clinical trials; and stable disease (SD) was observed in 11% resulting in a disease control rate (ORR+SD) of 22%. In 23 of the 79 patients with reduced dosing, dose omission was most probably caused by toxicity, whereas 56 patients had progressive disease before receiving all 4 treatment cycles. Immune-related adverse events (irAE) were reported in 30% of all treated patients, the occurrence of irAE correlated significantly with the probability of response to therapy and prolonged OS.In this named-patient program including heavily pretreated patients, the efficacy and tolerability of ipilimumab 3 mg/kg corresponds with findings from the confirmatory clinical trial.
EVALuna2:19484

Enhancing lentiviral transduction to generate melanoma-specific human T cells for cancer immunotherapy - Simon, Bianca; Harrer, Dennis C.; Thirion, Christian; Schuler-Thurner, Beatrice; Schuler, Gerold; Uslu, Ugur (Journal of Immunological Methods, 2019)
Introduction of a tumor antigen-specific T cell receptor (TCR) into patient-derived lymphocytes has already exhibited promising results for the treatment of melanoma and other malignancies in clinical trials. However, insufficient or unsuccessful ex vivo manufacturing of engineered T cells due to low expansion and/or transduction rate can still be observed in some patients. Thus, we isolated human CD8+ T cells from healthy donors and equipped them with a gp100-specific TCR using a lentiviral construct in combination with a novel chemical lentiviral transduction enhancer (Lentiboost) to increase the rate of transduced cells. Following experiments to determine the ideal multiplicity of infection (MOI) and to analyze the efficacy of the transduction enhancer using a GFP-encoding lentivirus, we analyzed in the next step the transduction rate, cell count, and functionality of gp100 TCR-transduced T cells, i.e. antigen-specific cytokine secretion and lytic capacity. In order to increase the number of transduced cells, antigen-specific stimulation was performed, either once for 1 week (1st activation) or twice for another week (2nd activation). In general, each cycle of antigen-specific stimulation resulted in expansion of TCR-positive cells, while no further significant increase of transduced cells was observed after 2nd activation. Cytokine production pattern of transduced cells after antigen encounter, however, revealed significant antigen-specific secretion of TNF and IFNγ after the 1st as well as the 2nd activation. Furthermore, TCR T cells, either activated once or twice, showed significant cytotoxicity towards antigen-positive tumor cells. Taken together, these results show that it is feasible to transduce human T cells using a lentiviral construct in combination with this novel lentiviral transduction enhancer, which shows potential in the growing field of cancer immunotherapy.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Adoptive T cell therapy; gp100; Lentiboost; Lentivirus; T cell receptor; Tumor antigen

Ex vivo expanded NK Cells from Melanoma Patients receive their Migration in a 3D Model and lyse autologous Melanoma Cells - Rossner, S.; Czerwinski, Tina; Mark, Christoph; Gross, S.; Karg, Margarete; Bosch, Jacobus J.; Schuler-Thurner, Beatrice; Fabry, Ben; Schuler, Gerold; Bosch-Voskens, C. (2018)
EVALuna2:34775

Ex vivo expanded NK cells up-regulate natural cytotoxicity receptors able to mediate autologous melanoma cell killing - Roessner, S.; Gross, S.; Karg, M.; Hamann, A.; Campana, D.; Schuler-Thurner, Beatrice; Bosch, Jacobus J.; Schuler, Gerold; Voskens, C. J. (2017)
EVALuna2:34314

Gene network-based and ensemble modeling-based selection of tumor-associated antigens with a predicted low risk of tissue damage for targeted immunotherapy - Lischer, Christopher; Eberhardt, Martin; Flamann, Cindy; Berges, Johannes; Güse, Esther; Wessely, Anja; Weich, Adrian; Retzlaff, Jimmy; Dörrie, Jan; Schaft, Niels; Wiesinger, Manuel; März, Johannes; et al. (Journal for ImmunoTherapy of Cancer, 2024)
Background Tumor-associated antigens and their derived peptides constitute an opportunity to design off-the-shelf mainline or adjuvant anti-cancer immunotherapies for a broad array of patients. A performant and rational antigen selection pipeline would lay the foundation for immunotherapy trials with the potential to enhance treatment, tremendously benefiting patients suffering from rare, understudied cancers. Methods We present an experimentally validated, data-driven computational pipeline that selects and ranks antigens in a multipronged approach. In addition to minimizing the risk of immune-related adverse events by selecting antigens based on their expression profile in tumor biopsies and healthy tissues, we incorporated a network analysis-derived antigen indispensability index based on computational modeling results, and candidate immunogenicity predictions from a machine learning ensemble model relying on peptide physicochemical characteristics. Results In a model study of uveal melanoma, Human Leukocyte Antigen (HLA) docking simulations and experimental quantification of the peptide–major histocompatibility complex binding affinities confirmed that our approach discriminates between high-binding and low-binding affinity peptides with a performance similar to that of established methodologies. Blinded validation experiments with autologous T-cells yielded peptide stimulation-induced interferon-γ secretion and cytotoxic activity despite high interdonor variability. Dissecting the score contribution of the tested antigens revealed that peptides with the potential to induce cytotoxicity but unsuitable due to potential tissue damage or instability of expression were properly discarded by the computational pipeline. Conclusions In this study, we demonstrate the feasibility of the de novo computational selection of antigens with the capacity to induce an anti-tumor immune response and a predicted low risk of tissue damage. On translation to the clinic, our pipeline supports fast turn-around validation, for example, for adoptive T-cell transfer preparations, in both generalized and personalized antigen-directed immunotherapy settings.
CRIS-Team Scopus Importer:2024-05-24

Generation of an oncolytic herpes simplex virus 1 expressing human MelanA - Boscheinen, Jan; Thomann, Sabrina; Knipe, David M.; Deluca, Neal; Schuler-Thurner, Beatrice; Gross, Stefanie; Dörrie, Jan; Schaft, Niels; Bach, Christian; Rohrhofer, Anette; Werner-Klein, Melanie; Schmidt, Barbara; et al. (Frontiers in Immunology, 2019)
Robust anti-tumor immunity requires innate as well as adaptive immune responses. We have shown that plasmacytoid dendritic cells develop killer cell-like activity in melanoma cell cocultures after exposure to the infectious but replication-deficient herpes simplex virus 1 (HSV-1) d106S. To combine this innate effect with an enhanced adaptive immune response, the gene encoding human MelanA/MART-1 was inserted into HSV-1 d106S via homologous recombination to increase direct expression of this tumor antigen. Infection of Vero cells using this recombinant virus confirmed MelanA expression by Western blotting, flow cytometry, and immunofluorescence. HSV-1 d106S-MelanA induced expression of the transgene in fibroblast and melanoma cell lines not naturally expressing MelanA. Infection of a melanoma cell line with CRISPR-Cas9-mediated knockout of MelanA confirmed de novo expression of the transgene in the viral context. Dependent on MelanA expression, infected fibroblast and melanoma cell lines induced degranulation of HLA-matched MelanA-specific CD8+ T cells, followed by killing of infected cells. To study infection of immune cells, we exposed peripheral blood mononuclear cells and in vitro-differentiated macrophages to the parental HSV-1 d106S, resulting in expression of the transgene GFP in CD11c+ cells and macrophages. These data provide evidence that the application of MelanA-encoding HSV-1 d106S could enhance adaptive immune responses and re-direct MelanA-specific CD8+ T cells to tumor lesions, which have escaped adaptive immune responses via downregulation of their tumor antigen. Hence, HSV-1 d106S-MelanA harbors the potential to induce innate immune responses in conjunction with adaptive antitumor responses by CD8+ T cells, which should be evaluated in further studies.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Cytotoxic T cell response; Herpes virus; Malignant melanoma; Oncolytic viruses; Vaccine

GMP-compliant human monocyte-derived dendritic cells for cancer vaccination generated by using the Quantum (R) hollow fiber bioreactor system - Uslu, Ugur; Uslu, U.; Erdmann, M.; Wiesinger, M.; Schuler, Gerold; Schuler-Thurner, Beatrice (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2020-01-28

Good Manufacturing Practice-Compliant Production and Lot-Release ofEx VivoExpanded Regulatory T Cells As Basis for Treatment of Patients with Autoimmune and Inflammatory Disorders - Wiesinger, Manuel; Stoica, Diane; Roessner, Susanne; Lorenz, Carmen; Fischer, Anika; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Scheffold, Alexander; Schuler-Thurner, Beatrice; Neurath, Markus; Schuler, Gerold; et al. (Frontiers in Immunology, 2017)
In recent years, the exploration of regulatory T cell (Treg)-based cellular therapy has become an attractive strategy to ameliorate inflammation and autoimmunity in various clinical settings. The main obstacle to the clinical application of Treg in human is their low number circulating in peripheral blood. Therefore,ex vivoexpansion is inevitable. Moreover, isolation of Treg bears the risk of concurrent isolation of unwanted effector cells, which may trigger or deteriorate inflammation upon adoptive Treg transfer. Here, we present a protocol for the GMP-compliant production, lot-release and validation ofex vivoexpanded Tregs for treatment of patients with autoimmune and inflammatory disorders. In the presented production protocol, large numbers of Treg, previously enriched from a leukapheresis product by using the CliniMACS®system, areex vivoexpanded in the presence of anti-CD3/anti-CD28 expander beads, exogenous IL-2 and rapamycin during 21 days. The expanded Treg drug product passed predefined lot-release criteria. These criteria include (i) sterility testing, (ii) assessment of Treg phenotype, (iii) assessment of non-Treg cellular impurities, (iv) confirmation of successful anti-CD3/anti-CD28 expander bead removal after expansion, and (v) confirmation of the biological function of the Treg product. Furthermore, the Treg drug product was shown to retain its stability and suppressive function for at least 1 year after freezing and thawing. Also, dilution of the Treg drug product in 0.9% physiological saline did not affect Treg phenotype and Treg function for up to 90 min. These data indicate that these cells are ready to use in a clinical setting in which a cell infusion time of up to 90 min can be expected. The presented production process has recently undergone on site GMP-conform evaluation and received GMP certification from the Bavarian authorities in Germany. This protocol can now be used for Treg-based therapy of various inflammatory and autoimmune disorders.
EVALuna2:33800

Hypertonicity-enforced BCL-2 addiction unleashes the cytotoxic potential of death receptors - Sirtl, Simon; Knoll, Gertrud; Dieu Thuy Trinh; Lang, Isabell; Siegmund, Daniela; Gross, Stefanie; Schuler-Thurner, Beatrice; Neubert, Patrick; Jantsch, Jonathan; Wajant, Harald; Ehrenschwender, Martin (Oncogene, 2018)
Attempts to exploit the cytotoxic activity of death receptors (DR) for treating cancer have thus far been disappointing. DR activation in most malignant cells fails to trigger cell death and may even promote tumor growth by activating cell death-independent DR-associated signaling pathways. Overcoming apoptosis resistance is consequently a prerequisite for successful clinical exploitation of DR stimulation. Here we show that hyperosmotic stress in the tumor microenvironment unleashes the deadly potential of DRs by enforcing BCL-2 addiction of cancer cells. Hypertonicity robustly enhanced cytotoxicity of tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) and other DR ligands in various cancer entities. Initial events in TRAIL DR signaling remained unaffected, but hypertonic conditions unlocked activation of the mitochondrial death pathway and thus amplified the apoptotic signal. Mechanistically, we demonstrate that hyperosmotic stress imposed a BCL-2-addiction on cancer cells to safeguard the integrity of the outer mitochondrial membrane (OMM), essentially exhausting the protective capacity of BCL-2-like pro-survival proteins. Deprivation of these mitochondrial safeguards licensed DR-generated truncated BH3-interacting domain death agonist (tBID) to activate BCL-2-associated X protein (BAX) and initiated mitochondrial outer membrane permeabilization (MOMP). Our work highlights that hyperosmotic stress in the tumor environment primes mitochondria for death and lowers the threshold for DR-induced apoptosis. Beyond TRAIL-based therapies, our findings could help to strengthen the efficacy of other apoptosis-inducing cancer treatment regimens.
EVALuna2:34786

Hypertonicity primes malignant melanoma cells for apoptosis - Calance, Diana Nicoleta; Steixner, Charlotte; Gross, Stefanie; Schuler-Thurner, Beatrice; Knoll, Gertrud; Ehrenschwender, Martin (Apoptosis, 2018)
The tumor environment critically influences responsiveness of cancer cells to chemotherapies, most of which activate the mitochondria-regulated (intrinsic) apoptotic cascade to kill malignant cells. Especially skin tumors encounter an environment with remarkable biophysical properties. Cutaneous accumulation of Na+ locally establishes osmotic pressure gradients in vivo (hypertonicity or hyperosmotic stress), but whether cutaneous hypertonicity is a factor that modulates the responsiveness of skin cancers to therapeutic apoptosis-induction has thus far not been investigated. Here, we show that hyperosmotic stress lowers the threshold for apoptosis induction in malignant melanoma, the deadliest form of skin cancer. Hypertonic conditions enforce addiction to BCL-2-like proteins to prevent initiation of the mitochondria-regulated (intrinsic) apoptotic pathway. Essentially, hyperosmotic stress primes mitochondria for death. Our work identifies osmotic pressure in the tumor microenvironment as a cell extrinsic factor that modulates responsiveness of malignant melanoma cells to therapy.
EVALuna2:34391

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Patterns of Response and Survival According to the Presence of Hepatic and Extrahepatic Metastasis - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Hohberger, Bettina; Kaehler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; et al. (Cancers, 2021)
Simple Summary This retrospective multicenter study examines the influence of hepatic and extrahepatic metastases on the response of immune checkpoint blockade (ICB) in patients with metastatic uveal melanoma. A better response to dual ICB was observed in the presence of extrahepatic metastases in two recently published phase II trials. Therefore, we investigated two cohorts with and without extrahepatic metastasis and have assembled a population of 178 patients treated with ICB. The survival of this large cohort of patients with advanced UM was more favorable than that reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only. Background: Since there is no standardized and effective treatment for advanced uveal melanoma (UM), the prognosis is dismal once metastases develop. Due to the availability of immune checkpoint blockade (ICB) in the real-world setting, the prognosis of metastatic UM has improved. However, it is unclear how the presence of hepatic and extrahepatic metastasis impacts the response and survival after ICB. Methods: A total of 178 patients with metastatic UM treated with ICB were included in this analysis. Patients were recruited from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of hepatic metastasis, two cohorts were compared: patients with liver metastasis only (cohort A, n = 55) versus those with both liver and extra-hepatic metastasis (cohort B, n = 123). Data were analyzed in both cohorts for response to treatment, progression-free survival (PFS), and overall survival (OS). The survival and progression probabilities were calculated with the Kaplan-Meier method. Log-rank tests, chi(2) tests, and t-tests were performed to detect significant differences between both cohorts. Results: The median OS of the overall population was 16 months (95% CI 13.4-23.7) and the median PFS, 2.8 months (95% CI 2.5-3.0). The median OS was longer in cohort B than in cohort A (18.2 vs. 6.1 months; p = 0.071). The best objective response rate to dual ICB was 13.8% and to anti-PD-1 monotherapy 8.9% in the entire population. Patients with liver metastases only had a lower response to dual ICB, yet without significance (cohort A 8.7% vs. cohort B 16.7%; p = 0.45). Adverse events (AE) occurred in 41.6%. Severe AE were observed in 26.3% and evenly distributed between both cohorts. Conclusion: The survival of this large cohort of patients with advanced UM was more favorable than reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only.
CRIS-Team WoS Importer:2021-07-23

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Re-Induction following Resistance or Toxicity - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Kähler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; et al. (Cancers, 2022)
Re-induction with immune checkpoint blockade (ICB) needs to be considered in many patients with uveal melanoma (UM) due to limited systemic treatment options. Here, we provide hitherto the first analysis of ICB re-induction in UM. A total of 177 patients with metastatic UM treated with ICB were included from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of ICB re-induction, two cohorts were compared: patients who received at least one ICB re-induction (cohort A, n = 52) versus those who received only one treatment line of ICB (cohort B, n = 125). In cohort A, a transient benefit of overall survival (OS) was observed at 6 and 12 months after the treatment start of ICB. There was no significant difference in OS between both groups (p = 0.1) with a median OS of 16.2 months (cohort A, 95% CI: 11.1–23.8) versus 9.4 months (cohort B, 95% CI: 6.1–14.9). Patients receiving re-induction of ICB (cohort A) had similar response rates compared to those receiving ICB once. Re-induction of ICB may yield a clinical benefit for a small subgroup of patients even after resistance or development of toxicities.
CRIS-Team Scopus Importer:2022-01-28
Keywords: CTLA-4; Immune checkpoint blockade; PD-1; Re-induction; Toxicity; Treatment resistance; Uveal melanoma

Immunogenic and tolerogenic effects of the chimeric IL-2-diphtheria toxin cytocidal agent Ontak(®) on CD25(+) cells - Lutz, Manfred B.; Baur, Andreas; Schuler-Thurner, Beatrice; Schuler, Gerold (OncoImmunology, 2014)
Ontak(®), a conjugate between IL-2 and a diphtheria toxin fragment, was recently investigated in cancer clinical trials aiming to kill CD25(+) regulatory T cells (Tregs). We found that the activity of Ontak(®) was more complex on Tregs and conventional T cells (Tconvs) than anticipated, including a novel strong influence on dendritic cells (DCs).
EVALuna2:19435

Immunotherapy of uveal melanoma: vaccination against cancer : Multicenter adjuvant phase 3 vaccination study using dendritic cells laden with tumor RNA for large newly diagnosed uveal melanoma - Schuler-Thurner, Beatrice; Bartz-Schmidt, K. -U.; Bornfeld, N.; Cursiefen, C.; Fuisting, B.; Grisanti, S.; Heindl, L. M.; Holbach, L.; Keserue, M.; Knorr, H.; Koch, K.; Kruse, Friedrich; et al. (Ophthalmologe, 2015)
Uveal melanomas are the most common malignant tumors of the eye. With modern molecular biological diagnostic methods, such as chromosome 3 typing and gene expression analysis, these tumors can be categorized into highly aggressive (monosomy 3, class II) and less aggressive forms. This molecular biological stratification is primarily important for determining the risk of these tumors as no therapy is currently available that is able to prevent or delay metastases. A randomized study of patients with a poor prognosis (monosomy 3) is currently being carried out in order to determine whether a cancer vaccine prepared from autologous (patient's own) dendritic cells and uveal melanoma RNA can prevent or delay progression and further metastases of this extremely aggressive form of cancer. Inclusion in the uveal melanoma study, which hopes to provide a potential therapeutic option for patients, is only possible if patients are referred to an institution that is able to manufacture and provide this vaccination before the patient is operated on or treated with radiation. Untreated tumor material is necessary for producing the vaccine on an individualized patient basis.
EVALuna2:19521

Liver-directed treatment is associated with improved survival and increased response to immune checkpoint blockade in metastatic uveal melanoma: results from a retrospective multicenter trial - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Eckstein, Markus; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; Loquai, Carmen; et al. (Frontiers of Medicine, 2023)
Metastases of uveal melanoma (UM) spread predominantly to the liver. Due to low response rates to systemic therapies, liver-directed therapies (LDT) are commonly used for tumor control. The impact of LDT on the response to systemic treatment is unknown. A total of 182 patients with metastatic UM treated with immune checkpoint blockade (ICB) were included in this analysis. Patients were recruited from prospective skin cancer centers and the German national skin cancer registry (ADOReg) of the German Dermatologic Cooperative Oncology Group (DeCOG). Two cohorts were compared: patients with LDT (cohort A, n = 78) versus those without LDT (cohort B, n = 104). Data were analyzed for response to treatment, progression-free survival (PFS), and overall survival (OS). The median OS was significantly longer in cohort A than in cohort B (20.1 vs. 13.8 months; P = 0.0016) and a trend towards improved PFS was observed for cohort A (3.0 vs. 2.5 months; P = 0.054). The objective response rate to any ICB (16.7% vs. 3.8%, P = 0.0073) and combined ICB (14.1% vs. 4.5%, P = 0.017) was more favorable in cohort A. Our data suggest that the combination of LDT with ICB may be associated with a survival benefit and higher treatment response to ICB in patients with metastatic UM.
CRIS-Team Scopus Importer:2023-07-21
Keywords: anti-CTLA-4; anti-PD-1; immune checkpoint blockade; liver-directed therapy; SIRT; uveal melanoma

Nectin-1 determines the susceptibility of malignant melanoma to oncolytic herpes simplex virus in vitro and in vivo - Schwertner, B.; Lindner, G.; Stauner, C. Toledo; Klapproth, E.; Magnus, C.; Rohrhofer, A.; Gross, S.; Schuler-Thurner, Beatrice; Oettl, V.; Feichtgruber, N.; Drexler, K.; Evert, K.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Nectin-1 expression correlates with the susceptibility of malignant melanoma to oncolytic herpes simplex virus in vitro and in vivo - Schwertner, Barbara; Lindner, Georg; Toledo Stauner, Camila; Klapproth, Elisa; Magnus, Clara; Rohrhofer, Anette; Gross, Stefanie; Schuler-Thurner, Beatrice; Öttl, Veronika; Feichtgruber, Nicole; Drexler, Konstantin; Evert, Katja; et al. (Cancers, 2021)
Talimogene laherparepvec (T-VEC), an oncolytic herpes simplex virus, is approved for intralesional injection of unresectable stage IIIB/IVM1a melanoma. However, it is still unclear which parameter(s) predict treatment response or failure. Our study aimed at characterizing surface receptors Nectin-1 and the herpes virus entry mediator (HVEM) in addition to intracellular molecules cyclic GMP-AMP synthase (cGAS) and stimulator of interferon genes (STING) as potential bio-markers for oncolytic virus treatment. In 20 melanoma cell lines, oncolytic activity of T-VEC was correlated with the expression of Nectin-1 but not HVEM, as evaluated via flow cytometry and immunohistochemistry. Knockout using CRISPR/Cas9 technology confirmed the superior role of Nectin-1 over HVEM for entry and oncolytic activity of T-VEC. Neither cGAS nor STING as evaluated by Western Blot and immunohistochemistry correlated with T-VEC induced oncolysis. The role of these biomarkers was retrospectively analyzed for the response of 35 cutaneous melanoma metastases of 21 patients to intralesional T-VEC injection, with 21 (60.0%) of these lesions respond-ing with complete (n = 16) or partial regression (n = 5). Nectin-1 expression in pretreatment biopsies significantly predicted treatment outcome, while the expression of HVEM, cGAS, and STING was not prognostic. Altogether, Nectin-1 served as biomarker for T-VEC-induced melanoma regression in vitro and in vivo.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Herpes simplex virus; Malignant melanoma; Nectin-1; Oncolytic; T-VEC

Ocular diseases in metastatic cutaneous melanoma: review of 108 consecutive patients in two German tertiary centers - Grajewski, Rafael S.; Schuler-Thurner, Beatrice; Mauch, Cornelia; Kreuzberg, Nicole; Koch, Konrad R.; Bergua, Antonio; Cursiefen, Claus; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2014)
To analyze the incidence and spectrum of ocular disease in patients with metastatic cutaneous melanoma.One hundred and eight consecutive patients with metastatic cutaneous melanoma were screened for ocular diseases using standardized eye examination, including measurement of visual acuity and intraocular pressure, slit-lamp examination, funduscopy in mydriasis, and spectral-domain optical coherence tomography (SDOCT) of the retina. Selected cases with atypical findings underwent electrophysiological studies. One patient was examined for hypercortisolism by a dexamethasone suppression test.Ocular diseases were found in 65 out of 108 patients (60 %) with metastatic cutaneous melanoma, significantly more often in older patients (p = 0.004). Cataract was present in 27 patients (25 %), pseudophakia in 22 patients (20 %), macular disease in 29 patients (28 %), diabetic retinopathy in ten patients (9 %), hypertensive retinal disease in 14 patients (13 %), retinal venous and arterial occlusive disease in three patients (3 %), optic neuropathy in four patients (4 %), and uveitis in one patient (1 %). Eight patients (8 %) had choroidal or iridal nevi, one patient (1 %) choroidal hemangioma, and one patient (1 %) choroidal metastasis. No patient had periocular neoplastic lesions. Paraneoplastic retinopathy manifesting as acute exudative polymorphous vitelliform maculopathy (AEPVM)-like disease was diagnosed in two patients (2 %) with multifocal central serous chorioretinopathy and development of vitelliform or fibrin-like subretinal deposits in one patient.Patients with metastatic cutaneous melanoma reveal ocular diseases with a spectrum similar to the normal population of this age range. Very rarely, uveal metastasis as well as paraneoplastic retinopathy can occur.
EVALuna2:19483

Preclinical evaluation of a combination of checkpoint blockade and dendritic cell vaccination against Merkel cell carcinoma - Sauerer, Tatjana; Gerer, K.; Hoyer, Stefanie; Erdmann, M.; Berking, Carola; Voll, R.; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Preclinical evaluation of NF-κB-triggered dendritic cells expressing the viral oncogenic driver of Merkel cell carcinoma for therapeutic vaccination - Gerer, Kerstin F.; Erdmann, Michael; Hadrup, Sine R.; Lyngaa, Rikke; Martin, Lena-Marie; Voll, Reinhard E.; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Hoyer, Stefanie; Dörrie, Jan (Therapeutic Advances in Medical Oncology, 2017)
BACKGROUND: Merkel cell carcinoma (MCC) is a rare but very aggressive skin tumor that develops after integration of a truncated form of the large T-antigen (truncLT) of the Merkel cell polyomavirus (MCV) into the host's genome. Therapeutic vaccination with dendritic cells (DCs) loaded with tumor antigens is an active form of immunotherapy, which intends to direct the immune system towards tumors which express the respective vaccination antigens. METHODS: Cytokine-matured monocyte-derived DCs of healthy donors and MCC patients were electroporated with mRNA encoding the truncLT. To permit major histocompatibility complex (MHC) class II next to class I presentation, we used an RNA construct in which the antigen was fused to a DCLamp sequence in addition to the unmodified antigen. To further improve their immunogenicity, the DCs were additionally activated by co-transfection with the constitutively active nuclear factor (NF)-κB activator caIKK. These DCs were used to stimulate autologous CD8+ T-cells or a mixture of CD4+ and CD8+ T-cells. Then the percentage of T-cells, specific for the truncLT, was quantified by interferon (IFN)γ ELISpot assays. RESULTS: Both the truncLT and its DCLamp-fusion were detected within the DCs by flow cytometry, albeit the latter required blocking of the proteasome. The transfection with caIKK upregulated maturation markers and induced cytokine production. After 2-3 rounds of stimulation, the T-cells from 11 out of 13 healthy donors recognized the antigen. DCs without caIKK appeared in comparison less potent in inducing such responses. When using cells derived from MCC patients, we could induce responses for 3 out of 5 patients; however, here the caIKK-transfected DCs did not display their superiority. CONCLUSION: These results show that optimized DCs are able to induce MCV-antigen-specific T-cell responses. Therapeutic vaccination with such transfected DCs could direct the immune system against MCC.
EVALuna2:34320

Proteasomes generate spliced epitopes by two different mechanisms and as efficiently as non-spliced epitopes - Ebstein, F.; Textoris-Taube, K.; Keller, C.; Golnik, R.; Vigneron, N.; Van Den Eynde, B. J.; Schuler-Thurner, Beatrice; Schadendorf, D.; Lorenz, F. K. M.; Uckert, W.; Urban, S.; Lehmann, A.; et al. (Scientific Reports, 2016)
Proteasome-catalyzed peptide splicing represents an additional catalytic activity of proteasomes contributing to the pool of MHC-class I-presented epitopes. We here biochemically and functionally characterized a new melanoma gp100 derived spliced epitope. We demonstrate that the gp100(mel)47-52/40-42 antigenic peptide is generated in vitro and in cellulo by a not yet described proteasomal condensation reaction. gp100(mel)47-52/40-42 generation is enhanced in the presence of the ?5i/LMP7 proteasome-subunit and elicits a peptide-specific CD8(+) T cell response. Importantly, we demonstrate that different gp100(mel)-derived spliced epitopes are generated and presented to CD8(+) T cells with efficacies comparable to non-spliced canonical tumor epitopes and that gp100(mel)-derived spliced epitopes trigger activation of CD8(+) T cells found in peripheral blood of half of the melanoma patients tested. Our data suggest that both transpeptidation and condensation reactions contribute to the frequent generation of spliced epitopes also in vivo and that their immune relevance may be comparable to non-spliced epitopes.
EVALuna2:19591

Retrospective interactive rigid fusion of 18F-FDG-PET and CT: Additional diagnostic information in melanoma patients - Römer, Wolfgang; Nömayr, Anton; Greess, Holger; Fiedler, Ekkehard; Platsch, Günter; Schuler-Thurner, Beatrice; Pfahlberg, Annette; Hothorn, Torsten; Schuler, Gerold; Hornegger, Joachim; Bautz, Werner; Kuwert, Torsten (Nuklearmedizin-Nuclear Medicine, 2006)
Aim: This study investigates whether interactive rigid fusion of routine PET and CT data improves localization, detection and characterization of lesions compared to separate reading. For this purpose, routine PET and CT scans of patients with metastases from malignant melanoma were used. Patients, methods: In 34 patients with histologically confirmed malignant melanoma, FDG-PET and spiral CT were performed using clinical standard protocols. For all of these patients, gold standard was available. Clinical and radiological follow-up identified 82 lesions as definitely pathological. Two board-certified nuclear medicine physicians and two board-certified radiologists analyzed PET and CT images independently from each other. For each patient up to 32 anatomical regions (24 lymph node regions, 8 extranodular regions) were systematically classified. Discordant areas were interactively analyzed in manually and rigidly registered images using a commercially available fusion tool. No side-by-side reading was performed. Results: Image fusion disclosed that the evaluation of the PET images alone led to a mislocalization in 26 of 91 focally FDG enhancing lesions. The overall sensitivities of PET, CT, and image fusion were 85, 88, and 94%, respectively; the overall specificities of PET, CT and image fusion were 98, 95 and 100%, respectively. Image fusion exhibited statistically significant higher specificity values as compared with CT. Ten definitely malignant sites were false-negative in CT, but could be detected by PET. On the other hand, twelve metastases were false-negative in PET, but could be detected by CT. These included two lesions, which had a clear correlate on the PET image when the fused images were evaluated. On the whole, registration of the PET and CT images yielded additional diagnostic information in 44% of the definitely malignant lesions. Conclusion: Retrospective image fusion of independently obtained PET and CT data is particularly valuable in exactly lodizing foci of abnormal FDG uptake and improves the detection of metastases of malignant melanoma. © 2006 Schattauer GmbH.

Safety and tolerability of a single infusion of autologous ex vivo expanded regulatory T cells in adults with ulcerative colitis (ER-TREG 01): protocol of a phase 1, open-label, fast-track dose-escalation clinical trial - Voskens, Caroline; Stoica, Diane; Roessner, Susanne; Vitali, Francesco; Zundler, Sebastian; Rosenberg, Marita; Wiesinger, Manuel; Wunder, Jutta; Siegmund, Britta; Schuler-Thurner, Beatrice; Schuler, Gerold; Berking, Carola; et al. (BMJ Open, 2021)
Introduction Accumulating evidence suggests that the adoptive transfer of ex vivo expanded regulatory T cells (Treg) may overcome colitogenic immune responses in patients with inflammatory bowel diseases. The objective of the ER-TREG 01 trial is to assess safety and tolerability of a single infusion of autologous ex vivo expanded Treg in adults with ulcerative colitis.
CRIS-Team WoS Importer:2021-12-24

Sarcoidosis Under Dendritic Cell Vaccination Immunotherapy in Long-term Responding Patients with Metastatic Melanoma - Uslu, Ugur; Erdmann, Michael; Schliep, Stefan; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Schuler-Thurner, Beatrice (Anticancer Research, 2017)
Sarcoidosis, a chronic inflammatory disorder, results from increased immune responses. Its development can be triggered in patients under immunotherapy, as activation of the immune system in these patients is desired. Since 1997, 249 patients with metastasized cutaneous melanoma (stage III and IV, AJCC 2009) have been treated with dendritic cell (DC)-based vaccines at our hospital. Three out of these patients were diagnosed with sarcoidosis after or during long-term DC vaccination therapy (1.20%). Metastatic disease was initially suspected based on the radiographic manifestation of lung masses or bilateral hilar lymphadenopathy. Histological assessment, however, revealed the appropriate diagnosis. Interestingly, all three patients are long-term responders and have remained free of metastatic or progressive disease for over a period of at least 4 years. In summary, sarcoidosis can occur in patients with cancer who have benefited from DC-based therapeutic vaccination and thus, its development, even with substantial delay, may be associated with successful anticancer immunotherapy.
EVALuna2:34321

Stability and activity of MCSP-specific chimeric antigen receptors (CARs) depend on the scFv antigen-binding domain and the protein backbone - Krug, Christian; Birkholz, Katrin; Paulus, Alexander; Schwenkert, Michael; Schmidt, Patrick; Hoffmann, Nicole; Hombach, Andreas; Fey, Georg; Abken, Hinrich; Schuler, Gerold; Schuler-Thurner, Beatrice; Dörrie, Jan; et al. (Cancer Immunology Immunotherapy, 2015)
Chimeric antigen receptor (CAR)-modified T cells emerged as effective tools in the immunotherapy of cancer but can produce severe on-target off-tissue toxicities. This risk can conceivably be overcome, at least partially, by transient transfection. The design of CARs, however, has so far not been optimized for use in non-permanent T cell modification. Here we compared the performance of T cells modified with three different first- and second-generation CARs, each specific for MCSP (HMW-MAA) which is commonly expressed by melanoma cells. Upon RNA transfer, the expression of all receptors was limited in time. The second-generation CARs, which combined CD28-CD3ζ signaling, were expressed at higher levels and more prolonged than first-generation CARs with CD3ζ only. The CD28 domain increased the cytokine production, but had only an indirect effect on the lytic capacity, by prolonging the CAR expression. Especially for the second-generation CARs, the scFv clearly impacted the level and duration of CAR expression and the T cell performance. Thus, we identified a CAR high in both expression and anti-tumor cell reactivity. T cells transfected with this CAR increased the mean survival time of mice after challenge with melanoma cells. To facilitate clinical application, this CAR was used to redirect T cells from late-stage melanoma patients by RNA transfection. These T cells mediated effective antigen-specific tumor cell lysis and release of pro-inflammatory cytokines, even after cryoconservation of the transfected T cells. Taken together, the analysis identified a CAR with superior anti-melanoma performance after RNA transfer which is a promising candidate for clinical exploration.
EVALuna2:19545

Step-by-step Improvement of mRNA-electroporated dendritic Cells in a Phase I / II Clinical Study in cutaneous Melanoma Patients: better Survival correlates with a higher Immunoscore and increased Expression of PEBP1 in the Blood - Dörrie, Jan; Schaft, Niels; Gross, S.; Ostalecki, Christian; Eberhardt, Martin; Vera-Gonzales, J.; Uslu, Ugur; Moreira, Alvaro; Koch, Elias; Kummer, Mirko; Erdmann, M.; Schliep, S.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Survival of metastatic melanoma patients after dendritic cell vaccination correlates with expression of leukocyte phosphatidylethanolamine-binding protein 1/Raf kinase inhibitory protein - Buschow, Sonja I.; Ramazzotti, Matteo; Reinieren-Beeren, Inge M. J.; Heinzerling, Lucie; Westdorp, Harm; Stefanini, Irene; Beltrame, Luca; Hato, Stanleyson V.; Ellebaek, Eva; Gross, Stefanie; Van Anh Nguyen; Weinlich, Georg; et al. (Oncotarget, 2017)
Immunotherapy for metastatic melanoma offers great promise but, to date, only a subset of patients have responded. There is an urgent need to identify ways of allocating patients to the most beneficial therapy, to increase survival and decrease therapy-associated morbidity and costs. Blood-based biomarkers are of particular interest because of their straightforward implementation in routine clinical care. We sought to identify markers for dendritic cell (DC) vaccine-based immunotherapy against metastatic melanoma through gene expression analysis of peripheral blood mononuclear cells. A large-scale microarray analysis of 74 samples from two treatment centers, taken directly after the first round of DC vaccination, was performed. We found that phosphatidylethanolamine binding protein 1 (PEBP1)/Raf Kinase inhibitory protein (RKIP) expression can be used to identify a significant proportion of patients who performed poorly after DC vaccination. This result was validated by q-PCR analysis on blood samples from a second cohort of 95 patients treated with DC vaccination in four different centers. We conclude that low PEBP1 expression correlates with poor overall survival after DC vaccination. Intriguingly, this was only the case for expression of PEBP1 after, but not prior to, DC vaccination. Moreover, the change in PEBP1 expression upon vaccination correlated well with survival. Further analyses revealed that PEBP1 expression positively correlated with genes involved in T cell responses but inversely correlated with genes associated with myeloid cells and aberrant inflammation including STAT3, NOTCH1, and MAPK1. Concordantly, PEBP1 inversely correlated with the myeloid/lymphoid-ratio and was suppressed in patients suffering from chronic inflammatory disease.
EVALuna2:34315

Targeting of DEC-205 on human dendritic cells results in efficient MHC class II-restricted antigen presentation - Birkholz, Katrin; Schwenkert, Michael; Kellner, Christian; Gross, Stefanie; Fey, Georg; Schuler-Thurner, Beatrice; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (Blood, 2010)
The use of dendritic cells (DCs) in therapeutic cancer vaccination requires their loading with tumor-specific antigen(s). DEC-205, a phagocytosis receptor mediating antigen uptake, is associated with CD8+ T-cell responses in mice. Here we fused an anti-DEC-205scFv to an HLA-DP4-restricted epitope from the tumor antigen MAGE-A3, and examined the suitability and efficacy of DEC-205 to deliver a helper epitope to human monocytederived DCs (moDCs). The construct specifically bound DEC-205 on human moDCs without negative impact on DC phenotype and function. We measured antigen presentation with specific autologous CD4+ T cells, generated by TCR-RNA transfection. DEC-205 targeting resulted in significant major histocompatibility complex class II-restricted antigen presentation, and was superior to loading DCs by electroporation of mRNA encoding endosome-targeted MAGE-A3-DCLAMP or by direct peptide pulsing. Anti-DEC-205scFv-MAGE-A3 was presented 100 times more efficiently than the control constructs. DC maturation before or during incubation with anti-DEC-205scFv-MAGE-A3 reduced the interleukin-10/interleukin- 2 ratio. Moreover, we successfully applied the DEC-205 targeting strategy to moDCs from malignant melanoma patients. Again, DEC-205-targeted mature DCs (mDCs) presented the antigen more efficiently than peptide-pulsed DCs and maintained their stimulatory capacity after cryoconservation. Thus, DEC-205 targeting represents a feasible and effective method to deliver helper epitopes to DCs in anticancer vaccine strategies, which may also be suitable for DC targeting in vivo. © 2010 by The American Society of Hematology.
CRIS-Team Scopus Importer:2021-10-01

The future of affordable cancer immunotherapy - Schaft, Niels; Dörrie, Jan; Schuler, Gerold; Schuler-Thurner, Beatrice; Sallam, Husam; Klein, Shiri; Eisenberg, Galit; Frankenburg, Shoshana; Lotem, Michal; Khatib, Areej (Frontiers in Immunology, 2023)
The treatment of cancer was revolutionized within the last two decades by utilizing the mechanism of the immune system against malignant tissue in so-called cancer immunotherapy. Two main developments boosted cancer immunotherapy: 1) the use of checkpoint inhibitors, which are characterized by a relatively high response rate mainly in solid tumors; however, at the cost of serious side effects, and 2) the use of chimeric antigen receptor (CAR)-T cells, which were shown to be very efficient in the treatment of hematologic malignancies, but failed to show high clinical effectiveness in solid tumors until now. In addition, active immunization against individual tumors is emerging, and the first products have reached clinical approval. These new treatment options are very cost-intensive and are not financially compensated by health insurance in many countries. Hence, strategies must be developed to make cancer immunotherapy affordable and to improve the cost-benefit ratio. In this review, we discuss the following strategies: 1) to leverage the antigenicity of “cold tumors” with affordable reagents, 2) to use microbiome-based products as markers or therapeutics, 3) to apply measures that make adoptive cell therapy (ACT) cheaper, e.g., the use of off-the-shelf products, 4) to use immunotherapies that offer cheaper platforms, such as RNA- or peptide-based vaccines and vaccines that use shared or common antigens instead of highly personal antigens, 5) to use a small set of predictive biomarkers instead of the “sequence everything” approach, and 6) to explore affordable immunohistochemistry markers that may direct individual therapies.
CRIS-Team Scopus Importer:2023-09-29
Keywords: adoptive cell therapy; affordable; biomarkers; immunohistochemistry; immunotherapy; microbiome; RNA-based vaccines

The Generation of CAR-Transfected Natural Killer T Cells for the Immunotherapy of Melanoma - Simon, Bianca; Wiesinger, Manuel; Maerz, Johannes; Wistuba-Hamprecht, Kilian; Weide, Benjamin; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (International Journal of Molecular Sciences, 2018)
Natural killer T (NKT) cells represent a cell subpopulation that combines characteristics of natural killer (NK) cells and T cells. Through their endogenous T-cell receptors (TCRs), they reveal a pronounced intrinsic anti-tumor activity. Thus, a NKT cell transfected with a chimeric antigen receptor (CAR), which recognizes a tumor-specific surface antigen, could attack tumor cells antigen-specifically via the CAR and additionally through its endogenous TCR. NKT cells were isolated from peripheral blood mononuclear cells (PBMCs), expanded, and electroporated with mRNA encoding a chondroitin sulfate proteoglycan 4 (CSPG4)-specific CAR. The CAR expression on NKT cells and their in vitro functionality were analyzed. A transfection efficiency of more than 80% was achieved. Upon stimulation with melanoma cells, CAR-NKT cells produced cytokines antigen-specifically. Compared with conventional CAR-T cells, cytokine secretion of CAR-NKT cells was generally lower. Specific cytotoxicity, however, was similar with CAR-NKT cells showing a trend towards improved cytotoxicity. Additionally, CAR-NKT cells could kill target cells through their endogenous TCRs. In summary, it is feasible to generate CAR-NKT cells by using mRNA electroporation. Their CAR-mediated cytotoxicity is at least equal to that of conventional CAR-T cells, while their intrinsic cytotoxic activity is maintained. Thus, CAR-NKT cells may represent a valuable alternative to conventional CAR-T cells for cancer immunotherapy.
EVALuna2:34785

The Generation of CAR-transfected NKT Cells for the Immunotherapy of Melanoma - Simon, B.; Wiesinger, M.; Marz, J.; Wistuba-Hamprecht, K.; Weide, B.; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (2018)
EVALuna2:34767

The Nectin-1 Expression correlates with the Susceptibility of malignant Melanoma to oncolytic Herpes Simplex Viruses in vitro and in vivo - Schwertner, B.; Linder, G.; Stauner, C. Toledo; Klapproth, E.; Magnus, C.; Rohrhofer, A.; Gross, S.; Schuler-Thurner, Beatrice; Oettl, V.; Feichtgruber, N.; Drexler, K.; Evert, K.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Therapeutic cancer vaccination with ex vivo rna-transfected dendritic cells—an update - Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Schuler-Thurner, Beatrice (Pharmaceutics, 2020)
Over the last two decades, dendritic cell (DC) vaccination has been studied extensively as active immunotherapy in cancer treatment and has been proven safe in all clinical trials both with respect to short and long-term side effects. For antigen-loading of dendritic cells (DCs) one method is to introduce mRNA coding for the desired antigens. To target the whole antigenic repertoire of a tumor, even the total tumor mRNA of a macrodissected biopsy sample can be used. To date, reports have been published on a total of 781 patients suffering from different tumor entities and HIV-infection, who have been treated with DCs loaded with mRNA. The majority of those were melanoma patients, followed by HIV-infected patients, but leukemias, brain tumors, prostate cancer, renal cell carcinomas, pancreatic cancers and several others have also been treated. Next to antigen-loading, mRNA-electroporation allows a purposeful manipulation of the DCs’ phenotype and function to enhance their immunogenicity. In this review, we intend to give a comprehensive summary of what has been published regarding clinical testing of ex vivo generated mRNA-transfected DCs, with respect to safety and risk/benefit evaluations, choice of tumor antigens and RNA-source, and the design of better DCs for vaccination by transfection of mRNA-encoded functional proteins.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Clinical trial; Dendritic cells; Electroporation; Immunotherapy; RNA; Therapeutic vaccination

The simultaneous siRNA-mediated downregulation of inhibitory receptors to improve CAR-T cell immunotherapy of melanoma - Simon, B.; Harrer, D.; Weide, B.; Schuler, Gerold; Schuler-Thurner, Beatrice; Dörrie, Jan; Schaft, Niels; Uslu, Ugur (2017)
EVALuna2:34317

The simultaneous siRNA-mediated downregulation of PD-1 and CTLA-4 to improve CAR-T cell immunotherapy of melanoma - Simon, B.; Harrer, D.; Schuler-Thurner, Beatrice; Dörrie, Jan; Schaft, Niels; Schuler, Gerold; Uslu, Ugur (2018)
EVALuna2:34395

The siRNA-mediated downregulation of PD-1 alone or simultaneously with CTLA-4 shows enhanced in vitro CAR-T-cell functionality for further clinical development towards the potential use in immunotherapy of melanoma - Simon, Bianca; Harrer, Dennis C.; Schuler-Thurner, Beatrice; Schaft, Niels; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (Experimental Dermatology, 2018)
Chimeric antigen receptor (CAR)-T cells have been used successfully for cancer immunotherapy. While substantial tumor regression was observed in leukaemia and lymphoma, CAR therapy of solid tumors needs further improvement. A major obstacle to the efficiency of engineered T cells is posed by triggering of inhibitory receptors, for example programmed cell death protein 1 (PD-1) and cytotoxic T lymphocyte-associated protein 4 (CTLA-4), leading to an impaired antitumor activity. To boost CAR-T-cell function, we co-electroporated T cells with both, mRNA encoding a CAR specific for chondroitin sulphate proteoglycan 4 (CSPG4) and small-interfering RNAs (siRNAs) to downregulate PD-1 (siPD-1) and CTLA-4 (siCTLA-4). Flow cytometry revealed that activation-induced upregulation of both PD-1 and CTLA-4 was suppressed when compared to CAR-T cells electroporated with negative control siRNA. The siRNA transfection showed no influence on CAR expression of engineered T cells. Functionality assays were performed using PD-L1- and CD80-transfected melanoma cells endogenously expressing CSPG4. CAR-T cells transfected with siPD-1 alone showed improvement in cytokine secretion. Additionally, CAR-T cells transfected with either siPD-1 alone or together with siCTLA-4 exhibited a significantly increased cytotoxicity. No or only little effects were observed when CAR-T cells were co-transfected with siCTLA-4 only. Taken together, it is feasible to optimize CAR-T cells by co-transfection of CAR-encoding mRNA and siRNAs to downregulate inhibitory receptors. Our in vitro data indicate an improvement of the functionality of these CAR-T cells, suggesting that this strategy could represent a novel method to enhance CAR-T-cell immunotherapy of cancer.
EVALuna2:34375

The transfection of natural killer T cells with a tumor-antigen specific chimeric antigen receptor (CAR) for melanoma immunotherapy - Simon, B.; Wiesinger, M.; Maerz, J.; Wistuba-Hamprecht, K.; Weide, B.; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Uslu, Ugur (EXPERIMENTAL DERMATOLOGY, 2019)
CRIS-Team WoS Importer:2019-03-26

Twelve-year survival and immune correlates in dendritic cell-vaccinated melanoma patients - Gross, Stefanie; Erdmann, Michael; Haendle, Ina; Voland, Steve; Berger, Thomas; Schultz, Erwin; Strasser, Erwin; Dankerl, Peter; Janka, Rolf Matthias; Schliep, Stefan; Heinzerling, Lucie; Sotlar, Karl; et al. (JCI Insight, 2017)
BACKGROUND: Reports on long-term (≥10 years) effects of cancer vaccines are missing. Therefore, in 2002, we initiated a phase I/II trial in cutaneous melanoma patients to further explore the immunogenicity of our DC vaccine and to establish its long-term toxicity and clinical benefit after a planned 10-year followup. METHODS: Monocyte-derived DCs matured by TNFα, IL-1β, IL-6, and PGE2 and then loaded with 4 HLA class I and 6 class II-restricted tumor peptides were injected intradermally in high doses over 2 years. We performed serial immunomonitoring in all 53 evaluable patients. RESULTS: Vaccine-specific immune responses including high-affinity, IFNγ-producing CD4+ and lytic polyfunctional CD8+ T cells were de novo induced or boosted in most patients. Exposure of mature DCs to trimeric soluble CD40 ligand, unexpectedly, did not further enhance such immune responses, while keyhole limpet hemocyanin (KLH) pulsing to provide unspecific CD4+ help promoted CD8+ T cell responses - notably, their longevity. An unexpected 19% of nonresectable metastatic melanoma patients are still alive after 11 years, a survival rate similar to that observed in ipilimumab-treated patients and achieved without any major (>grade 2) toxicity. Survival correlated significantly with the development of intense vaccine injection site reactions, and with blood eosinophilia after the first series of vaccinations, suggesting that prolonged survival was a consequence of DC vaccination. CONCLUSIONS: Long-term survival in advanced melanoma patients undergoing DC vaccination is similar to ipilimumab-treated patients and occurs upon induction of tumor-specific T cells, blood eosinophilia, and strong vaccine injection site reactions occurring after the initial vaccinations. TRIAL REGISTRATION: ClinicalTrials.gov NCT00053391. FUNDING: European Community, Sixth Framework Programme (Cancerimmunotherapy LSHC-CT-2006-518234; DC-THERA LSHB-CT-2004-512074), and German Research Foundation (CRC 643, C1, Z2).
EVALuna2:14632

Vaccination with dendritic Cells for metastasized Uveal Melanoma: immunological and clinical Responses - Moreira, Alvaro; Gross, S.; Uslu, Ugur; Dörrie, Jan; Kummer, Mirko; Schliep, S.; Sponagl, F.; Lischer, Christopher; Erdmann, M.; Heinzerling, Lucie; Schuler, Gerold; Schuler-Thurner, Beatrice (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13